2002
DOI: 10.1590/s1519-566x2002000200013
|View full text |Cite
|
Sign up to set email alerts
|

Influência do fotoperíodo na reprodução e longevidade de Orius insidiosus (Say) (Heteroptera: Anthocoridae)

Abstract: Effect of Photoperiod on Reproduction and Longevity of Orius insidiosus (Say) (Heteroptera: Anthocoridae) ABSTRACT-Orius insidiosus (Say) is an important predator of thrips and photoperiod can affect the reproduction of this insect. The objective of this work was to verify the occurrence of reproductive diapause in O. insidiosus in laboratory conditions. The experiments were carried out in environmental chambers, at photoperiods of 9L:15D, 10L:14D, 11L:13D, 12L:12D, 13L:11D and 14L:10D, temperature of 25±1ºC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
0
7
0
8
Order By: Relevance
“…Significant difference (P < 0.05) was found for egg number/female between 9h and 12h of light only. Argolo et al (2002) Mean female and male longevity of O. thyestes was similar among the 12L:12D, 11L:13D and 10L:14D photoperiods, but was significantly shorter (P < 0.05) at 09L:15D (Table 1). In general, males live from 36% to 49% less than females (Table 1).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Significant difference (P < 0.05) was found for egg number/female between 9h and 12h of light only. Argolo et al (2002) Mean female and male longevity of O. thyestes was similar among the 12L:12D, 11L:13D and 10L:14D photoperiods, but was significantly shorter (P < 0.05) at 09L:15D (Table 1). In general, males live from 36% to 49% less than females (Table 1).…”
Section: Resultsmentioning
confidence: 82%
“…Argolo et al (2002) observed a longer pre-oviposition period of O. insidiosus submitted to 11h of photofase and found a direct relation between the number of hours of light and the oviposition period of the predator.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Na cultura do crisântemo ocorrem vários insetos-praga que podem causar injúrias diretas e/ ou indiretas, exigindo, na maioria das vezes, a intervenção do produtor para promover a redução de suas populações a fim de se evitar prejuízos. O uso de inimigos naturais do gênero Orius (Wolff) tem despontado como tática viável para o manejo de pragas nessa cultura, pois são insetos pequenos, com alta capacidade de busca e estão presentes em locais da planta comuns aos de muitas pragas, aumentando as chances de encontro (BUENO, 2000;ARGOLO et al, 2002;MENDES et al, 2002;SILVEIRA et al, 2003).…”
Section: Introductionunclassified